The Relative Importance of Fungal Infection, Conspecific Density and Environmental Heterogeneity for Seedling Survival in a Dominant Tropical Tree. (20th May 2013) - Chanthorn, Wirong; Caughlin, Trevor; Dechkla, Sukhum; Brockelman, Warren Y.
Abstract: A gap remains in our understanding of how host‐specific fungal pathogens impact negative density dependence (NDD). Here, we investigated survival of Cinnamomum subavenium Miq. seedlings, the dominant canopy species in a seasonal tropical evergreen forest, Thailand. It is infected by a host‐specific fungus that is easily identifiable in the field. We quantified the effects of conspecific seedling and adult density on fungal infection and seedling survival over a wide range of environmental heterogeneity in elevation, understory vegetation and presence of forest gaps. Generalized linear mixed models (GLMMs) for seedling survival revealed that fungal infection significantly reduced survival and had the strongest effect on seedling survival as compared with conspecific density and environmental heterogeneity. Adult conspecific density was not, however, significantly correlated with the probability of infection, and conspecific seedling density was positively associated with increased infection only at high elevations. In contrast to infection, we found a significant positive correlation between conspecific seedling density and the probability of seedling survival. Consequently, our results demonstrate that fungal infection can have major impacts on seedling survival, but not in a manner consistent with local NDD effects on seedlings, as assumed in the Janzen–Connell hypothesis. Our study provides an example of how quantifying the interaction between environmental heterogeneity and a host‐specific plant‐pathogen can yield unexpected insights into the dynamics of seedling populations. The combined effects of host‐specific pathogens and environmental heterogeneity on survival of dominant seedling species may ultimately provide a chance for rarer species to recruit.